METHOD HALLIWICK: A PROPOSAL FOR THE TEACHING OF SWIMMING FOR PERSONS WITH DEFICIENCIES (Fiep Bulletin - online, 2014)
This article hopes to raise some aspects related to the practice of the Halliwick method as a method to teach survival in water, and from there going to conventional swimming. This study is an accumulation of experiences in trying to teach the method, while our teacher of Physical Education  and leader of the group, in the Program of Motor Activities for Deficient people (PROAMDE) are utilizing the methodology and philosophy in its total, and in these are included. "Happiness for being in the water" or "Felicidade por estar na água" .The individual accompaniment of an instructor for each swimmer, with no use of flotation objects, emphasis on abilities and not on the deficiencies , all are taught in a way to so they will learn the properties of the water and their affects on the body.  All are encouraged to improve but not pressured, and all are called by their first names, reinforcing the equality of each  one.  All this is a part of a program, based on the theoretical references of the creator of the method.  James McMillan.
Keywords: Deficiency; Halliwick; Swimming